An Evolutionary Game Theory-Based Framework for Analyzing Behavioral Strategies in Contractor–Owner Conflicts over Additional Construction Costs - Jeong, Seong Sik; Cha, Hee Sung; Yoon, Jong Han (Buildings, 2025)
The construction industry faces increasing conflicts over additional construction costs due to economic uncertainties, such as global pandemics and wars. These disputes often lead to project delays, legal actions, and even construction halts, causing significant financial and operational losses for stakeholders. To address these challenges, this study develops a simulation model based on evolutionary game theory (EGT) to identify the key influencing factors and applies the Analytic Hierarchy Process (AHP) to analyze and manage the conflicts between contractors and owners in private construction projects. The model quantifies decision-making dynamics by calculating the relative importance of various factors under different scenarios. A proof-of-concept simulation of the model reveals that cooperative evolution dynamics significantly decrease when the cost-sharing ratio reaches 0.5 for contractors and 0.9 for owners. Furthermore, the sensitivity analysis indicates that exceeding cost-sharing thresholds undermines cooperation, increasing the risk of disputes. Through this simulation, this study concludes that fostering mutual trust and informed decision-making on cost-sharing ratio significantly reduces project disputes and enhances the stakeholders’ profitability. The developed model and its framework serve as valuable tools for providing project stakeholders with actionable insights aimed at fostering strategic behaviors that minimize dispute-driven financial risks in construction projects.
Keywords: Additional construction; Analytic hierarchy; Behavior strategy; Construction costs; Construction dispute resolutions; Construction projects; Cost sharing; Decisions makings; Evolutionary game theory; Hierarchy process; analytic hierarchy process; behavior strategies; construction dispute resolution; evolutionary game theory